2021
DOI: 10.1021/acs.energyfuels.0c04333
|View full text |Cite
|
Sign up to set email alerts
|

N-Oxide Polyethers as Kinetic Hydrate Inhibitors: Side Chain Ring Size Makes the Difference

Abstract: The formation of gas hydrates in flow lines is one of the most severe problems for flow assurance in the gas and oil industry. Developing effective kinetic hydrate inhibitors (KHIs) to avoid the problem of gas hydrate formation has attracted widespread attention. In this study, a series of poly­(glycidyl amine N-oxide)­s (PGAOs) with 5–7-membered rings as side chains, poly­(pyrrolidine glycidyl amine N-oxide)­s (PPyrGAOs), poly­(piperidine glycidyl amine N-oxide)­s (PPiGAOs), and poly­(azepane glycidyl amine N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We also knew that amine oxide groups in polymers can give good KHI performance. One study showed that a series of polyamine oxides was significantly better as a KHI than the corresponding polyamines, as well as gave better water solubility . Therefore, we synthesized several amine oxides of the maleic polymers with dibutylamino head groups by reaction with hydrogen peroxide as previously described (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We also knew that amine oxide groups in polymers can give good KHI performance. One study showed that a series of polyamine oxides was significantly better as a KHI than the corresponding polyamines, as well as gave better water solubility . Therefore, we synthesized several amine oxides of the maleic polymers with dibutylamino head groups by reaction with hydrogen peroxide as previously described (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…They include homopolymers and copolymers of N -vinyllactams, N -isopropylmethacrylamide (NIPMAm), and hyperbranched poly­(esteramide)­s. ,, These polymers can adsorb onto the surface of the crystal hydrate as a pseudo-guest through the polymeric pendant group and can prevent or delay nucleation of the hydrate crystal. However, polymers with other hydrophilic groups besides amides have also been shown to have good KHI performance, especially polyamine oxides. The exact KHI mechanism is not fully understood, but it may be due to the strong hydrogen bonding afforded by both amides and amine oxides with water molecules aiding gas hydrate nucleation inhibition and crystal growth inhibition…”
Section: Introductionmentioning
confidence: 99%
“…Advanced surface science is a prerequisite for the development of targeted LDHIs. ,, As surface-active reagents, LDHIs adsorb on the surface of ensuing hydrate nuclei and retard their growth and/or aggregation. , This necessitates an insightful understanding of the interaction between LDHI molecules and the hydrate surface. , The attractive force between LDHI molecules and the hydrate surface (i.e., the driving force of LDHIs adsorption) acts within a subnanometer range, meaning that the adsorption process is dictated only by a few outmost water layers of the hydrate surface. Carver et al indicated that this driving force arises from the hydrogen bonding between hydrophilic sites of LDHI molecules and water molecules of the hydrate surface. , This mechanism applies to hydrate surfaces contacting a gas or hydrophobic environment.…”
Section: Applications In Sustainable Technologiesmentioning
confidence: 99%